STUDY OF BACTERIAL ASSOCIATED WITH KOLANUT SOIL PLANTATION AND WASTE LOOKING AT THEIR BENEFITS TO MAN AND HIS ENVIRONMENT (Nigerian Journal of Technology, 2018)
Microorganisms are regarded as the oldest and most abundant life form on earth and their importance to man cannot be over emphasized. They are the occupants and architect of the biosphere maintaining metabolic cycles essential for life. The aim of the study was to explore the benefits and detriments of bacteria associated with kolanut soil plantation and waste to man and the environment.  Bacterial was isolated from kolanut soil plantation, decayed, decaying and fresh kolanut waste (testa and husk) obtained from Ilara-Mokin (Ondo State) and Owena-Osun (Osun State), Nigeria following standard procedures. Thirteen isolates with distinctive morphological and physiological characteristics were identified using molecular techniques and Sanger sequencing was employed to detect labelled chain-terminating nucleotides that are incorporated by DNA polymerase during replication of the templates. The genus of bacteria identified included; Bacillus, Enterobacter, Citrobacter, Klebsiella, Pseudomonas, Marinobacter, Staphylococcus, Lysinibacillus, Providencia, Erwinia. The most dominant genus however was the Bacillus, Pseudomonas and Citrobacter. A good number of the bacteria isolated can be explored for production of products such as enzymes, use as biocontrols and for environmental cleanups. http://dx.doi.org/10.4314/njt.v37i4.36